Conversion of shares: the tax implications - Ferreira, Hanneri (Department of Commercial Law, 2026)
The current economic downturn has had far reaching consequences. In the South African context various Black Economic Empowerment transactions have been put in jeopardy as a result of declining turnover and profits. Preference shares held in many target companies are as a result being converted into ordinary shares to relieve pressure on the target companies by removing the obligation to pay preference dividends. This paper considers the capital gains tax consequences of such conversions. It is argued that the necessary elements needed to trigger a capital gains tax liability is are not present in such transactions. Based on the theory that an asset consists of a bundle of rights, it could be argued that on the conversion of a share, a disposal of certain rights take place as certain of the rights in that bundle is given up. However, considering the definition of the term 'asset' in the Eighth Schedule to the Income Tax Act, is it argued that no disposal takes place on the conversion of a share of a specific class into a different class. It is further argued that even if it is held that a disposal does take place on the conversion of the shares, no proceeds accrue or is received from the disposal. As a result, the necessary triggers for a capital gains tax liability are not present and the conversion of the shares does not have any adverse capital gains tax liability consequences.